Randomized control trial comparing the titanium osteosynthesis and the biodegradable osteosynthesis in mandibulotomy access. Issue 4 (13th February 2019) - Liu, Jian Nan; Ong, Hui Shan; Wang, Ming Yi; Wan, Kenneth; Qu, Xing Zhou; Zhang, Chen Ping
Abstract: Background: The clinical degradation rate and strength of biodegradable implant exposed to postoperative radiotherapy (PORT) are unknown. Methods: A prospective randomized control trial of 40 consecutive mandibulotomy patients randomly divided into titanium and biodegradable cohorts. All patients received PORT. The following parameters were compared: maximal mouth opening, occlusal force, center of force trajectory, occlusal status, radiographic evidence of bony union, mandibular function impairment questionnaire (MFIQ), overall satisfaction score, and complication rates. Results: Both the mandibular function and occlusal status parameter of the biodegradable and the titanium groups were not significantly difference. Biodegradable cohort showed better MFIQ scores ( P = .08) and overall satisfaction scores ( P = .64) but was not statistically significant. Of note, 40% of patients in the titanium cohort complained of plate palpability/cold intolerance and required plate removal ( P = .02); 10% of patients in the titanium cohort developed osteoradionecrosis. Conclusion: Biodegradable osteosynthesis is as reliable as titanium osteosynthesis for mandibulotomy fixation. PORT did not increase the complication rate in the biodegradable group.